Labahitha spiders (Arachnida: Araneae: Filistatidae) from islands in the Indian and Pacific Oceans - Magalhaes, Ivan L.F.; Berry, James W.; Koh, Joseph K.H.; Gray, Michael R. (European Journal of Taxonomy, 2022)
The genus Labahitha has hitherto comprised two species from peninsular Malaysia and Christmas Island (Australia). We here demonstrate that the genus is widespread in islands and territories across the Indian and Pacific Oceans, including the following species that have been previously assigned to other filistatid genera: Labahitha marginata (Kishida, 1936) comb. nov. (= Filistata bakeri Berland, 1938 syn. nov.), Labahitha garciai (Simon, 1892) comb. nov. (= Pritha heikkii Saaristo, 1978 syn. nov., = Pritha sechellana Benoit, 1978 syn. nov.), Labahitha nicobarensis (Tikader, 1977) comb. nov., Labahitha littoralis (Roewer, 1938) comb. nov., Labahitha insularis (Thorell, 1891) comb. nov., Labahitha sundaica (Kulczyński, 1908) comb. nov. (all transferred from Pritha, the latter three provisionally, pending re-examination of the type material); Labahitha fuscata (Nakatsudi, 1943) comb. nov. and Labahitha ryukyuensis (Ono, 2013) comb. nov. (both transferred from Tricalamus). Many of these species have been collected in synanthropic settings and from disparate islands thousands of kilometers apart. This suggests either high dispersal capabilities or, more likely, human-mediated introductions. At least L. marginata has been introduced to continental America. Two new species of Labahitha are described: Labahitha platnicki sp. nov. from New Caledonia and the Bismarck Islands and Labahitha incerta sp. nov. from Queensland, Australia. The male of Labahitha gibsonhilli (Savory, 1943) is reported for the first time. Wandella loloata sp. nov. is described from Papua New Guinea, representing the first record of this genus outside Australia. Pritha hasselti (Simon, 1906) from Indonesia is shown to be a Filistatinae, and thus the species is provisionally transferred back to Filistata.